Impaired declarative memory for emotional material following bilateral amygdala damage in humans - Adolphs, R; Cahill, L; Schul, R; Babinsky, R (Learning & memory (Cold Spring Harbor, N.Y.), 1997)
Everyday experience suggests that highly emotional events are often the most memorable, an observation supported by psychological and pharmacological studies in humans. Although studies in animals have shown that nondeclarative emotional memory (behaviors associated with emotional situations) may be impaired by lesions of the amygdala, little is known about the neural underpinnings of emotional memory in humans, especially in regard to declarative memory (memory for facts that can be assessed verbally). We investigated the declarative memory of two rare patients with selective bilateral amygdala damage. Both subjects showed impairments in long-term declarative memory for emotionally arousing material. The data support the hypothesis that the human amygdala normally enhances acquisition of declarative knowledge regarding emotionally arousing stimuli.